Contextualizing community crime control: race, geography, and configurations of control in four communities - Leverentz, Andrea M. (Criminology, 2017)
Criminology and urban sociology have long-standing interests in how neighborhoods and communities respond to and control crime. We build on the literature on social disorganization, collective efficacy, and new parochialism to develop a framework that explains how and why communities respond differently to crime. We draw on more than 2 years of comparative ethnographic data and 56 resident and stakeholder interviews on responses to crime in four communities in two states. We find that the intersections of racial composition, geography, and crime narratives in each place contributed to distinct community responses to crime. By analyzing these dynamics across the four sites, we propose three types of public–parochial partnerships that communities use to respond to crime: public alliances that rely primarily on public forms of control, tentative public–parochial partnerships that rely on tenuous connections with public institutions, and grassroots engagement with public institutions. We explain the emergence of these three approaches as patterned responses rooted in characteristics of local contexts, including racial composition and geographic isolation.